Effect of sarcosine on antioxidant parameters and metallothionein content in the PC-3 prostate cancer cell line - Cernei, Natalia; Zitka, Ondrej; Skalickova, Sylvie; Gumulec, Jaromir; Sztalmachova, Marketa; Rodrigo, Miguel Angel Merlos; Sochor, Jiri; Masarik, Michal; Adam, Vojtěch; Hubalek, Jaromir; Trnkova, Libuse; Kruseova, Jarmila; et al. (Oncology reports, 2013)
Sarcosine is currently one of the most discussed markers of prostate cancer. It is involved in amino acid metabolism and methylation processes that occur during the progression of prostate cancer. In this study, we monitored the effect of the addition of sarcosine (0; 10; 250; 500; 1,000 and 1,500 µM) in a time-dependent manner (0-72 h) on the PC-3 prostate cancer cell line. For the assessment of cell viability, the commonly used MTT test was employed. Furthermore, ion-exchange liquid chromatography was used for the determination of sarcosine content in the PC-3 cells. We also determined metallothionein (MT) levels by chip capillary electrophoresis and Brdicka reaction in the cells treated with sarcosine. Sarcosine levels in the cells increased in a concentration-dependent manner levels increased from only 270 nM with the lowest applied concentration of sarcosine (10 µM) to 106 µM with the highest applied concentration of sarcosine (1,500 µM). There was a marginal change observed in the MT concentration. Finally, the antioxidant activity of the PC-3 cells was determined using five different spectrophotometric methods [2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing ability of plasma (FRAP), free radicals, N,N-dimethyl-p-phenylenediamine (DMPD) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS)]. A significant negative correlation was observed between DPPH and FRAP (r=-0.68 at p<0.001) and between DMPD and ABST (r=-0.64 at p<0.001). Additionally, as regards the correlation between MT and DPPH, a significant positive trend (r=0.62 at p<0.001) was observed.
Keywords: Prostatic Neoplasms; metalothionein; sarkosin; Metallothionein; Biomarkers, Tumor; lidé; Cell Survival; Free Radical Scavengers; mužské pohlaví; viabilita buněk; scavengery volných radikálů; Male; nádorové biomarkery; Cell Line, Tumor; Sarcosine; nádory prostaty; nádorové buněčné linie; Humans